Role of mitophagy in ocular neurodegeneration - Brooks, Calvin D.; Kodati, Bindu; Stankowska, Dorota L.; Krishnamoorthy, Raghu R. (Frontiers in Neuroscience, 2023)
Neurons in the central nervous system are among the most metabolically active cells in the body, characterized by high oxygen consumption utilizing glucose both aerobically and anaerobically. Neurons have an abundance of mitochondria which generate adequate ATP to keep up with the high metabolic demand. One consequence of the oxidative phosphorylation mechanism of ATP synthesis, is the generation of reactive oxygen species which produces cellular injury as well as damage to mitochondria. Mitochondria respond to injury by fusion which serves to ameliorate the damage through genetic complementation. Mitochondria also undergo fission to meet an increased energy demand. Loss of mitochondria is also compensated by increased biogenesis to generate new mitochondria. Damaged mitochondria are removed by mitophagy, an autophagic process, in which damaged mitochondria are surrounded by a membrane to form an autophagosome which ultimately fuses with the lysosome resulting in degradation of faulty mitochondria. Dysregulation of mitophagy has been reported in several central nervous system disorders, including, Alzheimer’s disease and Parkinson’s disease. Recent studies point to aberrant mitophagy in ocular neurodegenerative disorders which could be an important contributor to the disease etiology/pathology. This review article highlights some of the recent findings that point to dysregulation of mitophagy and it’s underlying mechanisms in ocular neurodegenerative diseases, including, glaucoma, age-related macular degeneration and diabetic retinopathy.